A low migration and high conductive silver paste and preparation method thereof

By combining thiol-based curing agent with epoxy resin and conductive filler, covalent bonds are formed, which improves the silver migration resistance and conductivity of conductive silver glue, and solves the problem of silver migration in humid environments, achieving high Conductivity and stability.

CN115746762BActive Publication Date: 2024-12-24BEIJING UNIV OF CHEM TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211499768.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-11-28
Publication Date
2024-12-24
Estimated Expiration
2042-11-28

AI Technical Summary

Technical Problem

The existing conductive silver glue is prone to silver migration in humid environments, resulting in electrode short circuits and reliability problems. The preparation process of the existing methods is complex, costly and unstable in conductivity.

Method used

Using a combination of thiol-based curing agents, epoxy resin and conductive filler, the covalent bonds are formed with thiol groups and silver, which enhances the interaction between silver and resin matrix, improves the ability to resist silver migration, and passes specific molar and mass ratio ratios. Mixing and curing were carried out to prepare low-migration, high-conductive silver glue.

Benefits of technology

The silver migration resistance and conductivity of conductive silver glue is significantly improved, the tensile shear strength is increased, and the volume resistivity is stable, which reduces the time and resistivity of silver migration, and does not require additional additives.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115746762B_ABST
    Figure CN115746762B_ABST
Patent Text Reader

Abstract

The present invention discloses a low migration and high conductive silver paste and a preparation method thereof, and relates to the technical field of conductive silver paste preparation. The conductive silver paste is obtained by curing raw materials including the following components: epoxy resin, thiol curing agent, accelerator and conductive filler; the molar ratio of the epoxy resin to the thiol curing agent is (1-4):1; the mass ratio of the epoxy resin to the accelerator is (50-200):1; the mass ratio of the total mass of the epoxy resin, the thiol curing agent and the accelerator to the conductive filler is 1:(2.5-7). The present invention introduces a thiol curing agent without adding any additives. While the thiol curing agent is bonded to the epoxy resin, the covalent bond formed by the silver and the thiol group in the thiol curing agent also chemically bonds the silver filler to the resin network structure, which can improve the dispersion and bonding strength of silver, enhance the interaction between silver and the resin matrix, and thus improve the anti-silver migration ability of the conductive silver paste.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of conductive silver paste preparation, and more particularly to a low-migration and highly conductive silver paste and a preparation method thereof. Background Art

[0002] Conductive silver glue is a kind of polymer-based conductive composite material composed of resin matrix, curing agent, conductive silver filler, diluent and other additives. Its conductive properties are achieved through conductive fillers. It has certain adhesion and conductivity. It is used for bonding between electronic devices and is widely used in the electronics industry. However, during the actual application of conductive silver glue in humid environment conditions, silver migration will occur, resulting in short circuits between electrodes, causing failure of components or circuits, and leading to serious reliability problems.

[0003] At present, the methods for delaying the migration of conductive glue silver at home and abroad are roughly:

[0004] Lu Qinghua et al. obtained conductive powder by silver plating copper powder. The conductive adhesive made from the conductive powder has a silver migration resistance 100 times that of silver powder conductive adhesive. The problem with this method is that the ball milling process for silver plating copper powder is complicated, the price is too high, the curing temperature is high, the conductivity is poor and unstable.

[0005] The invention patent CN 114530274 A proposes a preparation of a silver migration resistant conductor paste. The method adds silver-based glass powder to the conductor paste to improve the silver migration resistance of the conductor paste while ensuring the various properties of the conductor paste. The problem with this method is that the preparation process of the silver-based glass powder is complicated, and the prepared conductive paste needs to be sintered at high temperature during use, which limits its application in medium and low temperature environments.

[0006] The methods for improving the resistance of conductive silver paste to silver migration at home and abroad include adding inhibitory organic solvents, placing a narrow strip of gold in the middle of the electrode, plating low-activity metals on the silver surface, adding low-activity metals, etc. The problems with these methods can be summarized as follows: complex preparation process, unstable product quality, high product cost, and low product conductivity. Summary of the invention

[0007] In order to solve the problems existing in the prior art, the present invention provides a low migration and high conductive silver paste and a preparation method thereof. The present invention introduces a thiol curing agent without adding any additives. Since the mercapto group in the thiol curing agent forms a strong interaction with silver, the interaction between silver and the resin matrix is ​​enhanced, thereby improving the anti-silver migration ability of the conductive silver paste, and the conductive silver paste also has a high conductivity.

[0008] One of the purposes of the present invention is to provide a low migration and highly conductive silver paste, wherein the conductive silver paste is obtained by curing raw materials including the following components:

[0009] Epoxy resin, mercaptan curing agent, accelerator and conductive filler;

[0010] The molar ratio of the epoxy resin to the thiol curing agent is (1-4):1;

[0011] The mass ratio of the epoxy resin to the accelerator is (50-200):1;

[0012] The mass ratio of the total mass of the epoxy resin, the thiol curing agent and the accelerator to the conductive filler is 1:(2.5-7).

[0013] Preferably, the molar ratio of the epoxy resin to the thiol curing agent is (1.5-3):1;

[0014] The mass ratio of the epoxy resin to the accelerator is (75-150):1;

[0015] The mass ratio of the total mass of the epoxy resin, the thiol curing agent and the accelerator to the conductive filler is 1:(4-6).

[0016] Preferably, the epoxy resin is a glycidyl ether type epoxy resin which is liquid at room temperature.

[0017] Preferably, the epoxy resin is at least one of bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, and 1,4-cyclohexane diglycidyl ether; more preferably, it is 1,4-cyclohexane diglycidyl ether.

[0018] Preferably, the thiol curing agent is a multifunctional thiol curing agent.

[0019] Preferably, the thiol curing agent is at least one of trimethylolpropane tris(3-mercaptopropionate) and pentaerythritol tetrakis(2-mercaptoacetic acid) ester; more preferably, pentaerythritol tetrakis(2-mercaptoacetic acid) ester.

[0020] Preferably, the conductive filler is 5-8 micron-sized flaky silver powder.

[0021] The accelerator may be an accelerator commonly used in the art, such as accelerator DMP30.

[0022] The interaction mechanism between the mercapto group and silver in the conductive silver paste of the present invention is as follows:

[0023]

[0024] By using a multifunctional thiol curing agent, while the thiol curing agent is bonded to the epoxy resin, the covalent bond formed between silver and the thiol group in the thiol curing agent also chemically bonds the silver filler to the resin network structure, which can improve the dispersion and bonding strength of silver.

[0025] The second object of the present invention is to provide a method for preparing low migration and high conductive silver paste, the method comprising:

[0026] The components except the conductive filler are mixed according to the amount, and then mixed with the conductive filler and cured to obtain the conductive silver paste.

[0027] The curing temperature is 120℃-180℃; the curing time is 1h-4h.

[0028] Preferably, the curing temperature is 135° C.-165° C.; and the curing time is 1.5 h-3 h.

[0029] The following solutions can be adopted:

[0030] (1) mixing epoxy resin, curing agent and accelerator at room temperature to obtain a conductive adhesive resin matrix;

[0031] (2) The resin matrix obtained in step (1) is mixed with the conductive filler at room temperature, and ground evenly to obtain a conductive silver paste before curing.

[0032] (3) Curing the pre-cured conductive silver paste obtained in step (2) at 120° C.-180° C. for 1 h-4 h to obtain the conductive silver paste.

[0033] The present invention introduces a thiol curing agent without adding any additives. When the thiol curing agent is bonded to the epoxy resin, the covalent bond formed by the silver and the mercapto group in the thiol curing agent also chemically bonds the silver filler to the resin network structure, which can improve the dispersion and bonding strength of silver, enhance the interaction between silver and the resin matrix, and thus enhance the anti-silver migration ability of the conductive silver paste, and the conductive silver paste also has high conductivity; the tensile test shows that as the silver filler content increases, the tensile shear strength of the conductive silver paste gradually increases within a certain content range, which is different from the general conductive paste whose tensile shear strength continues to decrease with the increase of silver content, which indicates that the bonded silver particles have a reinforcing effect on the resin system; the conductive silver paste prepared by the method of the present invention, when the silver filler content is 80% of the total mass of the conductive silver paste, the cured conductive silver paste undergoes silver migration after 1 hour; the volume resistivity is 8.44×10 -4 Ω·cm; its tensile shear strength is 3.34Mpa; when no silver filler is added, the tensile shear strength of the specimen is 1.83Mpa. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1This is a schematic diagram of the silver migration test;

[0035] First, two electrodes with a length of 20 mm, a width of 5 mm and a distance of 2 mm were printed on a glass plate with conductive silver glue. Figure 1 In the circuit shown, a small piece of filter paper is placed between the electrodes, and sufficient deionized water is dripped in. Then a certain voltage is applied, and a recorder is used to record the change of the voltage across the resistor R over time. When the power is turned on and the conductive glue strip does not undergo silver migration, the voltage meter shows 0; when silver migration occurs, a value appears on the voltage meter and changes over time.

[0036] Figure 2 Silver migration curves of the conductive silver pastes prepared in Example 1, Comparative Example 1 and Comparative Example 2;

[0037] from Figure 2 It can be seen that the ability of Example 1 to resist silver migration is greatly improved compared with Comparative Examples 1 and 2. Example 1 undergoes silver migration 1 hour after power-on; Comparative Example 1 undergoes silver migration in about 5 minutes; and Comparative Example 2 undergoes silver migration within 1 minute.

[0038] Figure 3 is a curve diagram showing the change of volume resistivity of the conductive silver paste prepared by the method of Example 1 as a function of filler content;

[0039] from Figure 3 It can be seen that when the filler content reaches 75% and above, the conductivity of the conductive adhesive tends to be stable; when the filler content is 80%, its volume resistivity is 8.44×10 -4 Ω·cm.

[0040] Figure 4 This is the sulfur element X-ray photoelectron spectrum of the conductive silver paste prepared in Example 1;

[0041] pass Figure 4 The results of sulfur peak separation of the conductive silver paste prepared in Example 1 show that there is a certain amount of free thiol or thioether with carbon atoms at both ends in the sample; in addition, there are sulfur-silver covalent bonds and silver sulfide in the system, indicating that there is a covalent effect between sulfur and silver. In addition, the overall binding energy of sulfur in the figure is high, which is due to the coordination of metal ions with sulfur, which reduces the electron cloud density of sulfur and enhances the positive charge of the core, indicating that there is a coordination effect between metal ions and sulfur.

[0042] Figure 5 This is the Ag element X-ray photoelectron spectrum of the conductive silver paste prepared in Example 1;

[0043] pass Figure 5The peak separation results of the silver element in the conductive silver paste prepared in Example 1 show that silver exists in a single state and a positive monovalent state. The positive monovalent state corresponds to the sulfur-silver covalent bond and silver sulfide, and the zero valence corresponds to the silver powder that only coordinates or does not participate in the interaction; thereby further verifying the covalent and coordination effects between sulfur and silver.

[0044] Figure 6 The following is a curve showing the shear strength of the conductive silver paste prepared by the methods of Example 1 and Comparative Example 1 as a function of filler content.

[0045] from Figure 6 It can be seen that in Example 1, due to the strong bonding between the resin matrix and silver, the addition of silver filler has a reinforcing effect. As the filler content increases, the shear strength of the system first increases and then decreases; while in Comparative Example 1, there is no bonding between the resin matrix and silver, and as the filler content increases, the shear strength of the system gradually decreases. DETAILED DESCRIPTION

[0046] The present invention is described in detail below in conjunction with specific drawings and embodiments. It is necessary to point out that the following embodiments are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the content of the present invention still fall within the scope of protection of the present invention.

[0047] The raw materials in the examples and comparative examples of the present invention are all commercially available products, and their specific information is as shown in Table 1:

[0048] Table 1

[0049]

[0050] Example 1

[0051] Take 1,4-cyclohexane diglycidyl ether and pentaerythritol tetra(2-mercaptoacetic acid) ester and mix them in a molar ratio of 2:1. Add accelerator DMP30 to the mixture so that the mass ratio of 1,4-cyclohexane diglycidyl ether to accelerator DMP30 is 100:1, and mix them evenly to obtain a resin matrix. The resin matrix is ​​further mixed with 5-8 micron flaky silver powder in a mass ratio of 1:4 to obtain a cured silver conductive adhesive. The cured silver conductive adhesive is cured at 150°C for 2h to obtain a conductive silver adhesive.

[0052] The prepared conductive silver paste was tested for volume resistivity according to ASTM D257-91 standard method. The test results showed that silver migration occurred after 1 hour, and the volume resistivity was 8.44×10 -4 Ω·cm. The tensile shear strength measured according to GB T 7124-2008 method is 3.34MPa.

[0053] Example 2

[0054] Take bisphenol A diglycidyl ether and pentaerythritol tetrakis (2-mercaptoacetic acid) ester and mix them at a molar ratio of 1.5:1. Add accelerator DMP30 to the mixture so that the mass ratio of bisphenol A diglycidyl ether to accelerator DMP30 is 75:1, and mix them evenly to obtain a resin matrix. The resin matrix is ​​further mixed with 5-8 micron flaky silver powder at a mass ratio of 1:5 to obtain a pre-cured conductive silver paste. The pre-cured conductive silver paste is cured at 135°C for 3h to obtain a conductive silver paste.

[0055] The prepared conductive silver paste was tested for volume resistivity according to ASTM D257-91 standard method. The test results showed that silver migration occurred after 55 min, and the volume resistivity was 8.56×10 -4 Ω·cm. The tensile shear strength measured according to GB T7124-2008 method is 3.15MPa.

[0056] Example 3

[0057] Take bisphenol F diglycidyl ether and trimethylolpropane tris(3-mercaptopropionic acid) ester and mix them in a molar ratio of 3:1. Add accelerator DMP30 to the mixture so that the mass ratio of bisphenol F diglycidyl ether to accelerator DMP30 is 150:1, and mix them evenly to obtain a resin matrix. The resin matrix is ​​further mixed with 5-8 micron flaky silver powder in a mass ratio of 1:6 to obtain a pre-cured conductive silver glue. The pre-cured conductive silver glue is cured at 165°C for 1.5h to obtain a conductive silver glue. The test results are:

[0058] The prepared conductive silver paste was tested for volume resistivity according to ASTM D257-91 standard method. The test results showed that silver migration occurred after 50 minutes, and the volume resistivity was 8.89×10 -4 Ω·cm. The tensile shear strength measured according to GB T7124-2008 method is 2.98MPa.

[0059] Example 4

[0060] Take 1,4-cyclohexane diglycidyl ether and pentaerythritol tetra(2-mercaptoacetic acid) ester and mix them in a molar ratio of 1:1. Add accelerator DMP30 to the mixture so that the mass ratio of 1,4-cyclohexane diglycidyl ether to accelerator DMP30 is 50:1, and mix them evenly to obtain a resin matrix. The resin matrix is ​​further mixed with 5-8 micron flaky silver powder in a mass ratio of 1:2.5 to obtain a pre-cured conductive adhesive. The pre-cured conductive silver adhesive is cured at 120°C for 4 hours to obtain a conductive silver adhesive.

[0061] The prepared conductive silver paste was tested for volume resistivity according to ASTM D257-91 standard method. The test results showed that silver migration occurred after 45 minutes, and the volume resistivity was 9.23×10 -4 Ω·cm. The tensile shear strength measured according to GB T7124-2008 method is 3.03MPa.

[0062] Example 5

[0063] 1,4-cyclohexane diglycidyl ether and pentaerythritol tetra(2-mercaptoacetic acid) ester were mixed at a molar ratio of 4:1. Accelerator DMP30 was added to the mixture so that the mass ratio of 1,4-cyclohexane diglycidyl ether to accelerator DMP30 was 200:1, and the mixture was evenly mixed to obtain a resin matrix. The resin matrix was further mixed with 5-8 micron flaky silver powder at a mass ratio of 1:7 to obtain a pre-cured conductive silver glue. The pre-cured conductive silver glue was cured at 180°C for 1h to obtain a conductive glue sample.

[0064] The prepared conductive silver paste was tested for volume resistivity according to ASTM D257-91 standard method. The test results showed that silver migration occurred after 48 minutes, and the volume resistivity was 1.02×10 -3 Ω·cm. The tensile shear strength measured according to GB T7124-2008 method is 2.75MPa.

[0065] Comparative Example 1

[0066] Take 1,4-cyclohexane diglycidyl ether and polyetheramine D230 and mix them at a molar ratio of 2:1. Add accelerator DMP30 to the mixture so that the mass ratio of 1,4-cyclohexane diglycidyl ether to accelerator DMP30 is 100:1, and mix them evenly to obtain a resin matrix. The resin matrix is ​​further mixed with 5-8 micron flaky silver powder at a mass ratio of 1:4 to obtain a pre-cured conductive silver paste. The pre-cured conductive silver paste is cured at 150°C for 2h to obtain a conductive silver paste.

[0067] The prepared conductive silver paste was tested for volume resistivity according to ASTM D257-91 standard method. The test results showed that silver migration occurred after 3 minutes, and the volume resistivity was 1.25×10 -3 Ω·cm. The tensile shear strength measured according to GB T7124-2008 method is 4.80MPa.

[0068] From the test results of Comparative Example 1 and Example 1, it can be seen that the content ratio of resin / curing agent / accelerator / filler in Comparative Example 1 and Example 1 is exactly the same, but the test results are different. Since the curing agent used in Comparative Example 1 is different from that in Example 1, the amine curing agent used in Comparative Example 1 cannot form a strong interaction with the silver filler, so the silver migration occurs very quickly, and the resistivity is also slightly higher than the value in Example 1. However, compared with mercaptan, the network after the epoxy resin and the amine are cross-linked is more rigid, so the tensile shear strength is higher.

[0069] Comparative Example 2

[0070] Take 1,4-cyclohexane diglycidyl ether and methyl hexahydrophthalic anhydride and mix them in a molar ratio of 1:2. Add accelerator DMP30 to the mixture so that the mass ratio of 1,4-cyclohexane diglycidyl ether to accelerator DMP30 is 100:1, and mix them evenly to obtain a resin matrix. The resin matrix is ​​further mixed with 5-8 micron flaky silver powder in a mass ratio of 1:4 to obtain a pre-cured conductive silver paste. The pre-cured conductive silver paste is cured at 150°C for 2h to obtain a conductive silver paste.

[0071] The prepared conductive silver paste was tested for volume resistivity according to ASTM D257-91 standard method. The test results showed that silver migration occurred after 1 minute, and the volume resistivity was 1.33×10 -3 Ω·cm. The tensile shear strength measured according to GB T7124-2008 method is 5.34MPa.

[0072] From the test results of Comparative Example 2 and Example 1, it can be seen that the reactive functional group content ratio of the resin / curing agent in Comparative Example 2 is the same as that in Example 1 (1,4-cyclohexane diglycidyl ether has two epoxy groups, pentaerythritol tetra(2-thioglycolic acid) ester has four thiol groups, and the anhydride methyl hexahydrophthalic anhydride has one anhydride group), and the resin / accelerator / filler content ratio is also exactly the same as that in Example 1, but the test results are different. Since the curing agent used in Comparative Example 2 is different from that in Example 1, the anhydride curing agent used in Comparative Example 2 cannot form a strong interaction with the silver filler, so the silver migration occurs very quickly, and the resistivity is also slightly higher than the value in Example 1. However, compared with mercaptan, the network after the epoxy resin and the anhydride are cross-linked is more rigid, so the tensile shear strength is higher.

Claims

1. A low migration and high conductive silver paste, characterized in that The conductive silver paste is obtained by curing the following raw materials: Epoxy resin, mercaptan curing agent, accelerator and conductive filler; The molar ratio of the epoxy resin to the thiol curing agent is (1-4):1; The mass ratio of the epoxy resin to the accelerator is (50-200): 1; The mass ratio of the total mass of the epoxy resin, the thiol curing agent and the accelerator to the conductive filler is 1:(2.5-7); The curing temperature is 120℃-180℃; the curing time is 1h-4h; The thiol curing agent is a multifunctional thiol curing agent; The conductive filler is 5-8 micron flaky silver powder.

2. The low migration and high conductive silver paste according to claim 1, characterized in that: The molar ratio of the epoxy resin to the thiol curing agent is (1.5-3):1; The mass ratio of the epoxy resin to the accelerator is (75-150):1; The mass ratio of the total mass of the epoxy resin, the thiol curing agent and the accelerator to the conductive filler is 1:(4-6).

3. The low migration and high conductive silver paste according to claim 1, characterized in that: The epoxy resin is a glycidyl ether type epoxy resin which is liquid at room temperature.

4. The low migration and high conductive silver paste according to claim 1, characterized in that: The epoxy resin is at least one of bisphenol A diglycidyl ether, bisphenol F diglycidyl ether, and 1,4-cyclohexane diglycidyl ether.

5. The low migration and high conductive silver paste according to claim 1, characterized in that: The thiol curing agent is at least one of trimethylolpropane tris(3-mercaptopropionate) and pentaerythritol tetrakis(2-mercaptoacetic acid) ester.

6. A method for preparing a low migration and highly conductive silver paste as claimed in any one of claims 1 to 5, characterized in that The method comprises: The components except the conductive filler are mixed according to the amount, and then mixed with the conductive filler and cured to obtain the conductive silver paste.

7. The method according to claim 6, characterized in that: The curing temperature is 120℃-180℃; the curing time is 1h-4h.

8. The preparation method according to claim 6, characterized in that: The curing temperature is 135℃-165℃; the curing time is 1.5h-3h.

Citation Information

Patent Citations

  • Silver migration resistant conductor paste

    CN114530274A

  • Low-temperature quick-curable conductive silver adhesive and preparation method thereof

    CN109575860A

  • Composite Ag conductive adhesive capable of effectively controlling Ag ion migration

    CN110760284A

  • Electroconductive adhesive

    JP2004182935A